Culturally-adapted cognitive behavioural therapy based intervention for maternal depression: a mixed-methods feasibility study - Sobia Khan; Karina Lovell; Farah Lunat; Yumna Masood; Sadia Shah; Barbara Tomenson; Nusrat Husain (BMC, 2019)
Abstract Background British Pakistanis are one of the largest ethnic minority groups living in the UK, with high rates of maternal depression being reported in this population. Evidence suggests that culturally-adapted Cognitive Behavioural Therapy (CBT)-based interventions for depression, may improve clinical outcomes and patient satisfaction. This study was conducted to develop and test the feasibility and acceptability of a culturally-adapted, CBT-based, manual-assisted intervention in British Pakistani mothers experiencing maternal depression. Methods A mixed-method feasibility study that included qualitative interviews followed by the development of a CBT-based intervention for mothers with mild to moderate depression. Following the qualitative interviews, a CBT-based intervention called the Positive Health Program (PHP) was developed and delivered consisting of 12-weekly sessions. A before and after design was used to explore the feasibility and acceptability of the Positive Health Programme. Results A culturally-adapted CBT-based group intervention (PHP) was acceptable to this group and improvements were reported in depression and health-related quality of life. The women's understanding of 'depression' as a general consensus was in physical terms, but with an onset triggered by psychosocial causes. The most commonly reported factors contributing to depression were marital disharmony, lack of social support, and financial difficulties. Past help offered was primarily antidepressants, which were not welcomed by most of the women. A lack of availability of culturally sensitive interventions and the limited cultural sensitivity of NHS staff was also reported. Conclusion This study provides preliminary evidence for the feasibility and acceptability of a CBT-based culturally-adapted group psychological intervention for British Pakistani mothers. Trial registration Study ethics registration number: 10/H1005/62 (University of Manchester).